2019
DOI: 10.1590/1980-57642018dn13-010004
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of cognitive screening for patients with cerebrovascular diseases A systematic review

Abstract: ABSTRACT. Screening instruments are ideal for acute clinical settings because they are easy to apply, fast, inexpensive and sensitive for specific samples. However, there is a need to verify the psychometric properties of screening in stroke patients. Objective: This study investigated the psychometric properties (methodological procedures) of cognitive screening for patients with cerebrovascular diseases. Methods: A systematic review of papers published on PsycINFO, Web of Knowledge, PubMed and Science Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 68 publications
0
20
0
1
Order By: Relevance
“…Both MMSE and MoCA are commonly used cognitive screening scales in stroke patients (Rodrigues et al., 2019). This study showed a ceiling effect of the MMSE, which was also reported in previous observations (Trzepacz, Hochstetler, Wang, Walker, & Saykin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both MMSE and MoCA are commonly used cognitive screening scales in stroke patients (Rodrigues et al., 2019). This study showed a ceiling effect of the MMSE, which was also reported in previous observations (Trzepacz, Hochstetler, Wang, Walker, & Saykin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…they miss about one fifth of cognitively impaired patients, a proportion which increases in mild PSCI. In addition, their specificity is also lower than 100%, 28,30,32 indicating that mildly decreased scores might be observed in subjects with normal comprehensive assessment. Score interpretation needs to take into account the first language, education level (for both tests) and age (for MoCA) 28,33 ; their scores might also be influenced by sensorymotor deficit, deficits in language and perception (hemi-neglect).…”
Section: How To Evaluate the Neuropsychological Status In Stroke Patimentioning
confidence: 98%
“…Few of these studies included comprehensive neuropsychological or neuroimaging assessment and analysis. This consortium and a more recent review on the psychometric properties of cognition measures used in all stroke types [60] acknowledge the challenges in harmonizing neuropsychological data where the criteria for defining cognitive impairment and assessment measures used remain heterogeneous. Addressing the differences in cognitive impairment profiles between ischaemic and haemorrhagic stroke is beyond the scope of this review.…”
Section: Comparing Cognitive Impairment Between Ich and Ischaemic Strokementioning
confidence: 99%